Health problems and stress in Information Technology and Business Process Outsourcing employees - V Padma; N N Anand; S. M. G. Swaminatha Gurukul; S. M. A. Syed Mohammed Javid; Arun Prasad; S Arun (Wolters Kluwer Medknow Publications, 2015)
Stress is high in software profession because of their nature of work, target, achievements, night shift, over work load. 1. To study the demographic profile of the employees. 2. To access the level of job stress and quality of life of the respondents. 3. To study in detail the health problems of the employees. All employees working in IT and BPO industry for more than two years were included into the study. A detailed questionnaire of around 1000 IT and BPO employees including their personal details, stress score by Holmes and Rahe to assess the level of stress and master health checkup profile were taken and the results were analysed. Around 56% had musculoskeletal symptoms. 22% had newly diagnosed hypertension,10% had diabetes, 36% had dyslipidemia, 54% had depression, anxiety and insomnia, 40% had obesity. The stress score was higher in employees who developed diabetes, hypertension and depression. Early diagnosis of stress induced health problems can be made out by stress scores, intense lifestyle modification, diet advice along with psychological counselling would reduce the incidence of health problems in IT sector and improve the quality of work force.